2013
DOI: 10.1055/s-0033-1356755
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Masticatory Function Using Bite Force Measurements in Patients Treated for Mandibular Fractures

Abstract: Bite force measurements are excellent criteria for assessment of masticatory efficiency. The purpose of this study was to assess the effect of mandibular fractures on the bite forces of patients treated for such fractures. Patients who were surgically treated for isolated mandibular fractures in the Department of Oral and Maxillofacial Surgery from January 2006 to December 2007 were included in the study. Patients were asked to bite on a bite force transducer on the first, fourth, sixth, and ninth postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…The presence of other fractures appears to negatively impact masticatory performance. Sybil et al reported comparable results and found that there was a reverse relationship between the bite force values and the number of fractures of the mandible. This is a plausible outcome, given the simple fact that it is more difficult to recover from multiple fractures than from a single fracture and, moreover, multiple fractures carry the associated risk for more biomechanical complications.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The presence of other fractures appears to negatively impact masticatory performance. Sybil et al reported comparable results and found that there was a reverse relationship between the bite force values and the number of fractures of the mandible. This is a plausible outcome, given the simple fact that it is more difficult to recover from multiple fractures than from a single fracture and, moreover, multiple fractures carry the associated risk for more biomechanical complications.…”
Section: Discussionmentioning
confidence: 85%
“…In the literature, there are reports describing masticatory function as an outcome measure after the treatment of condylar fractures. These studies mostly focus on particular elements, eg, bite force, chewing cycles or (distribution of) masticatory muscle activity . Though, it is said that masticatory performance is the outcome of complex simultaneous interrelationships in which, among others, the bite force and the height of mastication cycles are confirmed as key predictors .…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, when used in patients treated surgically for mandibular fractures, records of maximum occlusal forces act as excellent assessment criteria for restoration of skeletal architecture and repair and healing of masticatory soft tissues. 4 Farmand et al in 1992 developed the concept of 3D miniplates. 6 Their shape is based on the principle of the quadrangle as a geometrically stable configuration for support.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when used in patients treated surgically for mandibular fractures, records of maximum occlusal forces act as excellent assessment criteria for restoration of skeletal architecture and repair and healing of masticatory soft tissues. 4 There is a paradigm shift in the treatment of mandibular fractures, from the historical maxillomandibular fixation to the recent internal fixation systems. Of these Miniplates and reconstruction plates are commonly used to treat simple and comminuted fractures of mandible.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures of the mandible not only cause a change in the skeletal architecture but also lead to changes in the other components of the masticatory apparatus in the form of masticatory muscle tear or injury and neurovascular injuries. Surgical treatment of mandibular fractures aims at restoration of skeletal form of the mandible with a hope that normal function and esthetics would be restored (11).…”
Section: Introductionmentioning
confidence: 99%